Adventure Kingdom, vol. 1 - Foxe, Steve (Andrews McMeel Publishing, 2021)
"When Clark sneaks into Adventure Kingdom, all he wants is a peek at the remains of the once-magical theme park he loved as a kid-plus a cool livestream for his fans. But then he meets Karoline, the granddaughter of the park's creator, and the two of them discover that the magic of that place was never just an illusion. With the help of an enchanted coin and a talking monkey with questionable loyalties, they set off to find what they've both lost and rescue Karoline's mysterious granddad"--